Pengenalan Al-Quran - Salim Said Daulay; Adinda Suciyandhani; Sopan Sofian; Juli Julaiha; Ardiansyah Ardiansyah (Jurnal Ilmiah Wahana Pendidikan, 2023)
The Qur'an is the first and most important source of Islamic teachings according to the beliefs of Muslims and is acknowledged for its truth. As a guide for mankind, the Qur'an has functions including Al-Huda (guidance), Al-Furqan (differentiator between right and wrong), Al-Burhan (proof of truth), Al-Dzikr or Al-Tadzkirah (warning ), Al-Syifa (healing medicine), Al-Mau'idhah (advice, lessons), and Al-Rahmah (grace). This paper aims to reveal the Introduction to the Qur'an, namely in the form of how the Qur'an was revealed, the other names of the Qur'an, the function of the Qur'an, and the Surahs of the Al-Quran. The study used is a literature review (literature review), which is a search and summarizes some empirical literature that is relevant and in accordance with the theme. The literature used is in the form of books, the Koran, commentaries, scientific articles from national and international journals. The Al-Qur'an was revealed in three stages, the Al-Qur'an itself functions as revelation, guidance, corrector, guardian of the previous book, judge, and as an eraser of the previous Shari'a. The other names of the Qur'an are: Al-Kitab, Al-Furqan, Adz-dzikra, Al-Quran and Al-Hukmu.